Engineering Students' Industrial Internship Experience Perception and Satisfaction: Work Experience Scale Validation - Teresa Nogueira; José Magano; Eunice Fontão; Marina Sousa; Ângela Leite (MDPI AG, 2021)
An essential aspect of higher education institutions' academic curricula for engineering courses is the students' industrial internship programs. In the literature, it is well accepted that such programs provide valuable learning outcomes and increase the graduates' employment prospects. Thus, it is paramount to evaluate the internship programs' quality to identify opportunities to improve their design and implementation. However, that evaluation typically depends on self-designed academic assessment surveys of questionable validity. The purpose of this paper is to assess engineering students' perceptions of their internship experiences. For that purpose, the validation of a recently adapted version of the Work Experience Questionnaire (WEQ) was carried out on a sample of 447 engineering students that participated in industrial internship programs offered by Portuguese public universities and polytechnic schools. A confirmatory factor analysis was performed to confirm the suitability of the model proposed by the WEQ's authors on this study's sample. The psychometric qualities were evaluated through convergent and discriminant validity. The results showed that the model fit the sample well, and convergent and discriminant validity was established. The general competencies subscale was the most important for the participants-specifically, the competency of solving problems. Differences concerning the WEQ and gender, company size, and compensation were found and discussed. This study provides researchers in the field with a new tool validated explicitly for engineering students.